Three dimensional plastic-damage multidirectional fixed smeared crack approach for modelling concrete structures. (1st June 2017) - Edalat-Behbahani, A.; Barros, J.A.O.; Ventura-Gouveia, A.
Abstract: A constitutive model to simulate the behaviour up to the failure of concrete structures subjected to multiaxial loading is presented. The proposed model is based on the combination of 3D multidirectional fixed smeared crack model to simulate the crack initiation and propagation, and a plastic-damage model to account for inelastic compressive behaviour of the intact concrete between cracks. The adopted smeared crack model considers the possibility of having more than one crack of different orientation in the same integration point and in different evolution of the cracking process. The plasticity part accounts for the development of irreversible strains and volumetric strain in compression, whereas the strain softening and stiffness degradation of the material under compression are controlled by an isotropic strain based damage model. The constitutive model was included in the 3D solid finite element of the FEMIX computer code, and the model appraisal is performed by simulating experimental tests with structural reinforced concrete (RC) elements. The numerical simulations have predicted with good accuracy the load carrying capacity, deformation, crack pattern, and plastic (compressive) zones of all analyzed tests. A parametric study is also performed to appraise the sensitivity of the numerical simulations to the values adopted for the model parameters.